Pemanfaatan Koagulan Biji Asam Jawa Guna Memperbaiki Parameter BOD, COD, dan TSS Limbah Cair Industri Tahu - Andi Mohamad Yusuf; Ratnaningsih Ruhiyat; Rositayanti Hadisoebroto (ECOTAS, 2022)
The purpose of this study was to determine the effectiveness of tamarind seeds in removing pollutant parameters in tofu wastewater produced in the process of making tofu. The parameters to be reduced are BOD, COD, TSS, and turbidity. Variations in coagulant doses used in this study were: 2g/L, 3g/L, 4g/L, and 5g/L. With a coagulation speed of 200 rpm for 3 minutes and a flocculation speed of 120 rpm for 14 minutes with a settling time of 60 minutes. The results showed that tamarind seeds were able to reduce BOD, COD, TSS, and turbidity at a dose of 4 g/L with a pH of 8. The results showed a decrease in turbidity parameters with an initial value of 950 NTU to 151 NTU with an efficiency of 84% removal, TSS parameter with initial value of 662 mg/L becomes 143 mg/L with 78% removal efficiency, COD parameter with initial value of 2987 mg/L becomes 533 mg/L with 82% removal efficiency, and BOD parameter with initial value of 1994 mg/L to 361 mg/L with a removal efficiency of 82%. These results indicate that COD and BOD are still above the quality standards set by the government and further research is needed.